A permutation approach to the assignment of the configuration to diastereomeric tetrads by comparison of experimental and ab initio calculated differences in NMR data - Boratyński, Przemysław J. (Beilstein Journal of Organic Chemistry, 2017)
Scoring permutations of experimental chemical shift deviations and DFT/GIAO calculated deviations of isotropic shieldings for sets of four diastereomers can help to assign their relative configurations. This method was exercised on a set of diastereomeric Cinchona alkaloid derivatives, where 13C NMR data always identified the proper configuration. The presented approach is also an attempt to quantify the assignment by exclusion.
Keywords: GIAO; NMR; stereochemistry assignment